Food Deserts: Grocers - Condrey, Adam; Miller, Grant; Partin, Sara; Smee, Erin; Moberly, Benjamin; Wohaska, Emily F.; Drak, Micah; Smith, Dakota; Yu, Han; Joglekar, Shreepad; Hallaq, Tom G. (Kansas State University, 2018)
Flat sales, declining growth, and increased competition from large corporate chains are just some of the challenges faced by rural grocers. These rural grocers are a vital resource for the small-town residents they serve. Yet much of the fresh produce goes to waste because of grocers are often required to purchase larger quantities than they can sell.
Keywords: food deserts; rural communities; small businesses